Classification Schemes Revisited: Applications to Web Indexing and Searching - Broughton, Vanda; Lane, Heather (Journal of Internet cataloging, 2000)
Basic skills of classification and subject indexing have been little taught in British library schools since automation was introduced into libraries. However, development of the Internet as a major medium of publication lias stretched the capacity of search engines to cope with retrieval. Consequently, there has been interest in applying existing systems of knowledge organization to electronic resources. Unfortunately, the classification systems have been adopted without a full understanding of modern classification principles. Analy-tico-synthetic schemes have been used crudely, as in the case of the Universal Decimal Classification (UDC). The fully faceted Bliss Bibliographical Classification, 2nd edition (BC2) with its potential as a tool for electronic resource retrieval is virtually unknown outside academic libraries.